CAD/CAM robotics and factories of the future: (Narosa Publishing House, 2006)
This Conference focuses on areas like CAD/CAM, Robotics, Automation, Artificial, Intelligence, Advanced Manufacturing Technologies, Manufacturing Management, Artifical Intelligence, product Desgin and LifeCycle Management, Supply Chain and Logistics Management...